The Great Distance between the Written and the Living Constitution for Migrants and Refugees in the Mediterranean Territory - Fernanda Navas-Camargo; Myriam Sepulveda Lopez (Journal of Mediterranean Knowledge, 2018)
Constitutional rights are rarely addressed for the protection of migrants and refugees. In the past few years, the number of migrants and among those seeking asylum has been growing increasingly. A crisis has emerged and even though some nations showed empathy when the refugee inflow began to increase, throughout time those good deeds haven´t been done as expected. Long standing periods in refugee camps awaiting bureaucratic decisions, reception quotas not being met and new entrance barriers that have been build up. The present document aims to review the principles instated in the Constitutional Rights from European Mediterranean countries, to compare those proclamations with the current reality and the developed political tools installed by the European Union in response to the refugee crisis. It is expected to be able to raise a critical speech towards welcome mechanisms and to pursue the integration of the voices of the unheard when proposing new legal solutions.